De novo mutations in SCN1A are associated with classic Rett syndrome: a case report - Mari Wold Henriksen; Kirstine Ravn; Benedicte Paus; Stephen von Tetzchner; Ola H Skjeldal (BMC, 2018)
Abstract Background Rett syndrome (RTT) is a neurodevelopmental disorder. In more than 95% of females with classic RTT a pathogenic mutation in MECP2 has been identified. This leaves a small fraction of classic cases with other genetic causes. So far, there has not been reported any other gene that may account for the majority of these cases. Case presentation We describe two females who fulfill the diagnostic criteria for classic RTT, with pathogenic de novo mutations in SCN1A, which usually leads to Dravet syndrome. The developmental history and clinical features of these two females fits well with RTT, but they do have an unusual epileptic profile with early onset of seizures. Investigation of mRNA from one of the females showed a significantly reduced level of MECP2 mRNA. Conclusions To our knowledge, this is the first report suggesting that SCN1A mutations could account for a proportion of the females with classic RTT without MECP2 mutations. As a consequence of these findings SCN1A should be considered in the molecular routine screening in MECP2-negative individuals with RTT and early onset epilepsy.